Ten Surprising Facts About Stressful Life Events and Disease Risk. [article]. - Cohen, Sheldon
After over 70 years of research on the association between stressful life events and health, it is generally accepted that we have a good understanding of the role of stressors in disease risk. In this review, we highlight that knowledge but also emphasize misunderstandings and weaknesses in this literature with the hope of triggering further theoretical and empirical development. We organize this review in a somewhat provocative manner, with each section focusing on an important issue in the literature where we feel that there has been some misunderstanding of the evidence and its implications. Issues that we address include the definition of a stressful event, characteristics of diseases that are impacted by events, differences in the effects of chronic and acute events, the cumulative effects of events, differences in events across the life course, differences in events for men and women, resilience to events, and methodological challenges in the literature. -- (from the author)